The Influence of Israiliyyat on Interpretation (Analysis of the Book of Tafsir Al-Qur'an Al-'Azim Ibn Kathir) - Zakka, Umar; Lutfianto, M.; Lita, Wang; Limei, Sun (Journal International Dakwah and Communication, 2021)
This research is backgrounded by knowing that many of the stories that Jews and Christians put into the book of interpretation aimed to undermine the interpretation itself is called israilliyat. It is known that this Israiliyyat is a science they have that is full of religious stories that they adhered to in ancient times. This research focuses on the influence of israiliyyat on the interpretation of the analysis of the qur'an al-'azim by Ibn Kathir. The method used in this research is library research, which is research conducted by reviewing literature and other sources. Meanwhile, the data collection techniques in this study use literature techniques, namely literature research carried out by reading, studying, and recording from various literature or materials that are in accordance with the subject matter. Then it is filtered and connected with the theoretical shell of thought. Ibn Kathir in discussing israiliyyat in the book of interpretation of the Qur'an al-az{im Kerena in many found damaging stories against an interpretation because the truth has not been found whether it is clear the source is from the Qur'an and hadith or not. It is known that israiliyyat it is not all wrong. first, israiliyyat according to the Islamic religion which can be taken because it is sourced from the Qur'an and hadith, secondly israiliyyat which cannot be taken by Muslims because it is not based on the Qur'an and hadith and the third israiliyyat which is indeed corroborated by Islamic sources and is not denied but for this we as Islamic ummah are obliged to be silent. With the story above, what Ibn kathir thinks about israiliyyat.